Предмет: Алгебра, автор: danikamarggalinov135

9 + 2(7х + 6) = 5х + 12
16 – 3(4х + 5) = 7(2х – 3)
6х – 2(5х + 4) = 1 – 7(4х + 3)
8(2x – 1) – 2(8x – 3) = –2

Ответы

Автор ответа: alexandrafastovez
0

Ответ:

1) х= -1

2) х = 11/13

3) х = -1/2

4) у уравнение несконченное количество ответов

Объяснение:

9 + 2 (7х + 6) = 5х + 12

9 + 14х + 12 = 5х + 12

14х - 5х = 12 - 12 - 9

9х = -9

х = -1

16 - 3 (4х + 5) = 7 (2х - 3)

16 - 12х - 15 = 14х - 21

-12х - 14х = -21 + 15 - 16

-26х = -22

х = 22/26

х= 11/13

6х - 2 (5х + 4) = 1 - 7 (4х + 3)

6х - 10х - 8 = 1 - 28х - 21

6х - 10х + 28х = -21 - 1 + 8

32х = -16

х = -16/32

х= -1/2

8 (2х - 1) - 2 (8х - 3) = - 2

16х - 8 - 16х + 6 = -2

16х - 16х = -2 - 6 + 8

у уравнение несконченное количество ответов

Похожие вопросы